Severe Aortic Stenosis Mimicking STE-ACS at Hospital in Remote Areas: A Case Report - Abas, Istiana Hairiah; Fabanyo, Fira Ardianti; Abubakar, Megawati; Fikri (Universitas Airlangga, 2024)
Highlights: 1. The value of a detailed physical assessment in patients with angina pectoris is crucial, as emphasized in this report. - Background: This case highlights the need for a comprehensive and accurate physical examination in patients with angina pectoris. Case Summary: A 46-year-old man was admitted to the hospital with chest pain and anterior ST segment elevation on electrocardiogram. Given the limited drugs and equipment in remote hospitals, initial treatment for ACS was given immediately. However, no significant improvement was seen with this treatment. An echocardiogram was performed right away and the results showed a severe AVS. B-blockers, ACE-I, diuretics, and MRA antagonists were administered, and the patient had good clinical results, and was recommended for immediate referral to a hospital with primary facilities for valve replacement surgery. Conclusion: Severe AVS can cause subendocardial ischemia, so the clinical findings may correspond to ACS. A thorough physical examination allows us to provide more accurate treatment.